A COMPREHENSIVE REVIEW ON “THE MULTIFACETED WORLD OF MONOCLONAL ANTIBODIES: A DETAILED EXPLORATION OF THEIR MECHANISMS, ENGINEERING STRATEGIES, APPLICATIONS, AND FUTURE PROSPECTS” - Sakshi Sharma; Salil Sanghvi; Mangal Singh Panwar (Journal of Global Pharma Technology, 2026)
Monoclonal antibodies are lab made proteins designed to function like   a normal antibodies. Monoclonal antibodies (mAb) have revolutionized medicine by providing targeted and personalized means of disease treatment. The mAb has found its way into the clinic for the treatment of cancer, autoimmune disorders, infectious diseases, and inflammatory conditions. Their specific recognition and inactivation of disease targets has not only enhanced curative effects but also minimized off-target effects relative to traditional drugs. There are still challenges to overcome, however, such as high costs of manufacturing, immunogenicity, and delivery restrictions. In the future, advancements in genetic engineering and biotechnology hold the promise to make them safer, more effective, and cost-effective. This review captures the present status of monoclonal antibodies and offers a perspective on their future role in designing next-generation therapies. Keywords: Monoclonal antibodies (mAbs), Future prospective, Therapeutic applications, Immunotherapy, Hybridoma technology.